2007
DOI: 10.3402/ljm.v2i3.4711
|View full text |Cite
|
Sign up to set email alerts
|

PubMed Medical publications from Libya

Abstract: Medical research and publications are the back-bone for advancing the medical field. We identified the Pubmed medical publications that are affiliated with Libya to shed some light on the contribution of this country's medical community to the PubMed database. All publications affiliated with Libya in the PubMed were counted over a five year period ending December 2006. We also used the same method to obtain data on the PubMed medical publications from Tunisia, Morocco and Yemen. Tunisia had the largest number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…8 Libya ranked lower than Morocco, Tunisia and Yemen in total number of PubMed publications between 2002 and 2006. 9 The same result was found when the data were normalized to gross domestic product (GDP). 9 Shaban and Abu-Zidan studied the medical publications from 20 Arab countries.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…8 Libya ranked lower than Morocco, Tunisia and Yemen in total number of PubMed publications between 2002 and 2006. 9 The same result was found when the data were normalized to gross domestic product (GDP). 9 Shaban and Abu-Zidan studied the medical publications from 20 Arab countries.…”
Section: Discussionsupporting
confidence: 59%
“…9 The same result was found when the data were normalized to gross domestic product (GDP). 9 Shaban and Abu-Zidan studied the medical publications from 20 Arab countries. Libya ranked 12th in the average annual publication rate, 10th when the data were normalized to the population and 15th when normalized to GDP.…”
Section: Discussionsupporting
confidence: 59%
“…It is worth noting that the scientific production of the MENA is low in general, and that of Libya is extremely low (1416). Several nations conduct regular cross-sectional studies on representative samples of their population to assess the health needs of their respective populations.…”
Section: Oral Health Research and Publications – The Recent Presentmentioning
confidence: 99%
“…Access to the contents of African journals is provided in part by the international bibliographic databases: African Index Medicus (AIM), EMBASE, MEDLINE/Pubmed, Scopus, and Web of Science (Gaillard, 1992) A number of bibliometric studies have examined scientific publications in sub-Saharan Africa as a whole (Arvantis et al, 2000;Hassan, 2001;Uthman et al, 2007;Tijssen, 2007;Hofman et al, 2009) and specific African countries including Malawi (Gondwe et al, 2008), Libya (Bakoush et al, 2007) and Egypt (Afifi, 2007). The results of these studies showed that scientific research in Africa is going through a crisis and that national scientific communities in these countries are struggling to sustain their activities.…”
Section: Introductionmentioning
confidence: 99%